NETRALITAS BIROKRASI DAN KUALITAS PELAYANAN PUBLIK - Ida Hayu Dwimawanti (Jurnal Manajemen Kepegawaian, 2009)
In order to create the quality of public service, so bureucracy neutrality as a principle must be done. Therefore, it is necessary the profesional, responsible, reliable, and fair government officer through construction done based on job performance and carrier system focused on system of job performance. The effort is written in number 43 of Laws in 1999 that regulates about pronciples of officers and number 37 of government regulation in 2004 about prohibition for government officer to be the member of political party.